"Digitally Oriented Materials": Focus on Lithium Disilicate Ceramics - Fernando Zarone; Marco Ferrari; Francesco Guido Mangano; Renato Leone; Roberto Sorrentino (Hindawi Limited, 2016)
The present paper was aimed at reporting the state of the art about lithium disilicate ceramics. The physical, mechanical, and optical properties of this material were reviewed as well as the manufacturing processes, the results of in vitro and in vivo investigations related to survival and success rates over time, and hints for the clinical indications in the light of the latest literature data. Due to excellent optical properties, high mechanical resistance, restorative versatility, and different manufacturing techniques, lithium disilicate can be considered to date one of the most promising dental materials in Digital Dentistry.